2020
DOI: 10.1051/0004-6361/202037582
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal line broadening due to braiding-induced turbulence in solar coronal loops

Abstract: Aims. Emission line profiles from solar coronal loops exhibit properties that are unexplained by current models. We investigate the non-thermal broadening associated with plasma heating in coronal loops that is induced by magnetic field line braiding. Methods. We describe the coronal loop by a 3D magnetohydrodynamic model of the turbulent decay of an initially-braided magnetic field. From this, we synthesised the Fe XII Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…As stated in section 2.2.3, non-thermal line broadening can vary significantly depending on the event, with loops showing average values between 5-10 km s −1 only (Antolin et al, 2015;Kriginsky et al, 2021) while others show values of 8-16 km s −1 (with a tail up to 22 km s −1 ), that is, on the same order or larger than the thermal component Froment et al (2020), see Figure 10. It is interesting to note that the 15-20 km s −1 range is common in active region loops with temperatures between 1 MK and 5 MK (Chae et al, 1998;Hara and Ichimoto, 1999;Brooks and Warren, 2016;Testa et al, 2016), and also with that obtained from models based on either MHD waves (Shi et al, 2021) or field-line braiding (Pontin et al, 2020), which suggests that the same level of turbulence can be found in loops with or without TNE. In other words, and rather counter-intuitively, the TNE process (which is known to induce strong flows along the loop), does not necessarily lead to higher levels of turbulence.…”
Section: Implication For the Energetics Variability And Morphology Of...mentioning
confidence: 52%
“…As stated in section 2.2.3, non-thermal line broadening can vary significantly depending on the event, with loops showing average values between 5-10 km s −1 only (Antolin et al, 2015;Kriginsky et al, 2021) while others show values of 8-16 km s −1 (with a tail up to 22 km s −1 ), that is, on the same order or larger than the thermal component Froment et al (2020), see Figure 10. It is interesting to note that the 15-20 km s −1 range is common in active region loops with temperatures between 1 MK and 5 MK (Chae et al, 1998;Hara and Ichimoto, 1999;Brooks and Warren, 2016;Testa et al, 2016), and also with that obtained from models based on either MHD waves (Shi et al, 2021) or field-line braiding (Pontin et al, 2020), which suggests that the same level of turbulence can be found in loops with or without TNE. In other words, and rather counter-intuitively, the TNE process (which is known to induce strong flows along the loop), does not necessarily lead to higher levels of turbulence.…”
Section: Implication For the Energetics Variability And Morphology Of...mentioning
confidence: 52%
“…12a). It was recently shown by Pontin et al (2020) that the spectral properties of synthesised line profiles from simulations of braiding-induced turbulence are consistent with key properties of observed spectra from coronal emission lines, including the magnitude of the non-thermal broadening and its scaling with intensity as well as the non-Gaussian nature of the spectra. The studies described in this section represent only a start in determining the consistency of the braiding mechanism with observations of the hot corona.…”
Section: Plasma Response and Consistency With Observationsmentioning
confidence: 58%
“…10c and e reveal that in general the axial flows are organized on larger spatial scales (across the loop) ranging from several hundred kilometers up to 2 Mm). This is in contrast to Pontin et al (2020), whose loop models lack the dynamics along the guide field because they do not include the interaction with the chromosphere and thus evaporation of plasma that drives the parallel flows. Hence, Pontin et al (2020) find a strong deviation from isotropy with the axial speeds being much smaller than the flow speeds perpendicular to the loop axis.…”
Section: Isotropy Of the Velocity Amplitudementioning
confidence: 97%